Plastik Sanatlarda Kuramsal Bakış Açılarıyla Resim - Yıldırım, Dila; Kılıç, Ahmet Göktuğ; Soylu, Rasim; Kızılırmak Çekinmez, Buse; Ayan, H. Müjde; Atlı, Çağatay; Gönülay Çalımlı, Zeynep; Öz Çelikbaş, Eda; Yalı, Fatih; Haykır, Mustafa; Vargün, Özlem; Keleş, Nurgül; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-